Absorbing Shocks: National Rainy-Day Funds and Cross-Country Transfers in a Fiscal Union - Timothy J. Goodspeed (Center for Economic Studies and ifo Institute (CESifo), 2016)
In this paper we investigate the interplay between national rainy-day funds and supra-national transfers in a fiscal union. Given that the EU has established rules limiting deficits, national rainy-day funds could in theory provide a way for countries to obey the rules and use fiscal policy, yet avoid using austerity measures during a recession. The rainy-day fund is self-insurance and we examine the funding of a national rainy-day fund for a country in isolation. We then introduce a fiscal union while allowing member countries to retain some fiscal policy control. We find that moral hazard leads to lower contributions to a rainy day fund with a fiscal union present, and further that the higher the fiscal transfer, the lower will be the contributions to the rainy-day fund. The optimal size of the fiscal union trades-off the ex-post insurance provided by the union and the moral hazard which reduces national ex-ante preparation for stabilization policies. Optimally, the insurance provided by the fiscal union should be lower (1) the more effective is own-fiscal policy; (2) the more the presence of the fiscal union reduces rainy-day fund savings; (3) the lower is the relative probability of recession; and (4) the lower is the utility gain of redistribution in the union. We also find that commitment to a transfer policy is essential. A fiscal union that is prone to break the rules on transfers negatively impacts the ex-ante contributions to individual members' rainy day funds.
Keywords: E60; H10; H60; H70; 330; fiscal union; fiscal transfers; federation; rainy-day funds; fiscal stabilization